Tensions regarding Self-Knowledge from (and beyond) the BNCC - Alves, Flávio Soares [UNESP]; Menezes, Potyra Curione [UNESP]; de Sande, Wesley Aleixo [UNESP]; Pereira, William Olielo [UNESP]; da Silva, Crislaine [UNESP] (FapUNIFESP (SciELO), 2024)
This article brings reflections on self-knowledge in school physical education. To this end, it proposes to tighten its framework within the BNCC, which is understood as a socio-emotional competence linked to the construction of school students' identities. From this point, it brings self-knowledge closer to physical education and the Life Project proposal, then outlines discussions woven in alliance with Eastern philosophy, the stylistics of existence, and the philosophy of difference. And finally, it problematizes self-knowledge in school physical education, seeking to highlight the role of body movement in enabling the conceptual inflections triggered here.
Tensionamentos acerca do Autoconhecimento a partir (e além) da BNCC
Keywords: Aesthetics of Existence; General Competencies (BNCC); Philosophy of Difference; School Physical Education; Self-knowledge